2023
DOI: 10.1097/md.0000000000035126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of opioid-free anesthesia on the incidence of postoperative nausea and vomiting: A meta-analysis of randomized controlled studies

Yanan Zhang,
Dandan Ma,
Bao Lang
et al.

Abstract: Background: Research on opioid-free anesthesia has increased in recent years; however, it has never been determined whether it is more beneficial than opioid anesthesia. This meta-analysis was primarily used to assess the effect of opioid-free anesthesia compared with opioid anesthesia on the incidence of postoperative nausea and vomiting. Methods: We searched the electronic databases of PubMed, the Cochrane Library, Web of Science and Embase from 2014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
1
0
0
Order By: Relevance
“…Previous studies have found that opioid-free anesthesia can reduce postoperative nausea and vomiting in patients (Frauenknecht et al, 2019;Salomé et al, 2021;Feenstra et al, 2023;Malo-Manso et al, 2023;Zhang et al, 2023) and improve the quality of postoperative recovery (Feenstra et al, 2023), which is consistent with the results of this meta-analysis of opioid-free gynecological surgery. But two meta-analyses found that opioid-free anesthesia reduced postoperative pain in patients (Malo-Manso et al, 2023;Zhang et al, 2023) and one showed that opioid-free anesthesia reduced extubation time (Zhang et al, 2023), which is different from our results.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have found that opioid-free anesthesia can reduce postoperative nausea and vomiting in patients (Frauenknecht et al, 2019;Salomé et al, 2021;Feenstra et al, 2023;Malo-Manso et al, 2023;Zhang et al, 2023) and improve the quality of postoperative recovery (Feenstra et al, 2023), which is consistent with the results of this meta-analysis of opioid-free gynecological surgery. But two meta-analyses found that opioid-free anesthesia reduced postoperative pain in patients (Malo-Manso et al, 2023;Zhang et al, 2023) and one showed that opioid-free anesthesia reduced extubation time (Zhang et al, 2023), which is different from our results.…”
Section: Discussionsupporting
confidence: 91%
“…Similar observations were made in a recent randomized trial on women having gynecological surgeries with OFA achieved using esketamine and dexmedetomidine [26]. A recent meta-analysis claiming data from 14 RCTs compared opioid-free vs. opioid-based anesthesia and noted a lower PONV [relative risk 0.41, 95% confidence interval (95% CI): 0.33-0.51] [15]. On a closer look, we see that the largest contribution came from a retrospective cohort study [27], and the number of PONV patients inflated by 10 in the opioid group [15].…”
Section: Opioid-free Anesthesia and Proposed Benefitssupporting
confidence: 71%
“…Appreciating that there are procedurespecific differences in postoperative outcomes, it may be best to consider agents based on surgical procedure. Even this is problematic, as the choice is arbitrary with no attempts to be consistent [15]. Laparoscopic cholecystectomy is a good example.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation